1980
DOI: 10.1111/j.1471-4159.1980.tb11222.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Production by Rat Brain In Vivo

Abstract: H2 O2 production by rat brain in vivo was observed with a method based on the measurement of brain catalase. The administration to the rat of 3‐amino‐1, 2, 4‐triazole, an H2 O2‐ dependent inhibitor of catalase, caused progressive inhibition of brain catalase activity in both the supernatant and pellet fractions of homogenates of the striatum and prefrontal cortex. The prevention of catalase inhibition by prior administration of ethanol confirmed that catalase inhibition in vivo was dependent upon H2 O2. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…As for the in vitro results, midbrain cell differentiation and proliferation were dose-dependently inhibited by C60, and these harmful effects were partly associated with the toxicities of the active oxygen species produced by C60. Sinet et al [10] reported that hydrogen peroxide can induce tissue damage, and such damage should be considered as a component in pathological processes such as the rapid brain ageing seen in Down's syndrome or Alzheimer's disease or in For the measurement of cell differentiation and proliferation, the degrees of staining were measured following the procedure described by Tsuchiya et al [7]. Individual control neuronal cell foci counted by dissecting microscopy (differentiation) and the control optical density measured by neutral red staining method (cell proliferation) were regarded as 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As for the in vitro results, midbrain cell differentiation and proliferation were dose-dependently inhibited by C60, and these harmful effects were partly associated with the toxicities of the active oxygen species produced by C60. Sinet et al [10] reported that hydrogen peroxide can induce tissue damage, and such damage should be considered as a component in pathological processes such as the rapid brain ageing seen in Down's syndrome or Alzheimer's disease or in For the measurement of cell differentiation and proliferation, the degrees of staining were measured following the procedure described by Tsuchiya et al [7]. Individual control neuronal cell foci counted by dissecting microscopy (differentiation) and the control optical density measured by neutral red staining method (cell proliferation) were regarded as 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Then, hydrogen peroxide is converted to water molecules by either GSH-Px or catalase enzymes (23). Due to the very low activity of catalase enzymes in the brain, GSH-Px is the main enzyme that causes the detoxification of hydrogen peroxide in the neural system (24).…”
Section: Discussionmentioning
confidence: 99%
“…With each assay a suitable blank which contained no H20 = and a control which contained l ml sodium azide, a catalase inhibitor, were included. Values were expressed as Units/ GmHb (14).…”
Section: Catalase Activitymentioning
confidence: 99%